2017
DOI: 10.3390/ijerph14040386
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in an Indian Rural Community: A ‘One-Health’ Observational Study on Commensal Coliform from Humans, Animals, and Water

Abstract: Antibiotic-resistant bacteria are an escalating grim menace to global public health. Our aim is to phenotype and genotype antibiotic-resistant commensal Escherichia coli (E. coli) from humans, animals, and water from the same community with a ‘one-health’ approach. The samples were collected from a village belonging to demographic surveillance site of Ruxmaniben Deepchand (R.D.) Gardi Medical College Ujjain, Central India. Commensal coliforms from stool samples from children aged 1–3 years and their environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 28 publications
(36 reference statements)
7
55
0
Order By: Relevance
“…The frequent use of quinolones group of antibiotics for treatment of enteric infections caused by gram-negative bacteria, could explain the high (25-40%), resistance of detected MDR E.coli against quinolones. We have previously shown that the frequency of resistance, co-resistance and resistance genes are high and similar in coliforms from humans and their environment [26,32]. Also, as previously seen the ESBL-producing E. coli isolates from river-water and -sediment belonged to phylogenetic groups A and B1 to which commensal E. coli are classified [26,32,33].…”
Section: Antibiotics Tested River-water N (%) River-sedimentn (%)supporting
confidence: 66%
See 1 more Smart Citation
“…The frequent use of quinolones group of antibiotics for treatment of enteric infections caused by gram-negative bacteria, could explain the high (25-40%), resistance of detected MDR E.coli against quinolones. We have previously shown that the frequency of resistance, co-resistance and resistance genes are high and similar in coliforms from humans and their environment [26,32]. Also, as previously seen the ESBL-producing E. coli isolates from river-water and -sediment belonged to phylogenetic groups A and B1 to which commensal E. coli are classified [26,32,33].…”
Section: Antibiotics Tested River-water N (%) River-sedimentn (%)supporting
confidence: 66%
“…We have previously shown that the frequency of resistance, co-resistance and resistance genes are high and similar in coliforms from humans and their environment [26,32]. Also, as previously seen the ESBL-producing E. coli isolates from river-water and -sediment belonged to phylogenetic groups A and B1 to which commensal E. coli are classified [26,32,33]. Thus, the emergence of MDR in E. coli and the other commensal coliform may also pose a risk for the emergence of new multi resistant pathogen.…”
Section: Antibiotics Tested River-water N (%) River-sedimentn (%)mentioning
confidence: 56%
“…It is estimated over 100 million Indian residents carry NDM-1 bacteria as normal gut flora (Walsh and Toleman 2012), which is harmless in the gut but can be lethal if they spread to other parts of the body and cause infection. If such figures are alarming, equally worrying is that even when we know some of the key drivers behind antibiotics resistance, what remains unclear are the complex transmission 'routes of resistant bacteria, as well as resistance genes and the impact of antibioticselective pressures in various reservoirs (animals, humans, and the environment)' (Purohit et al 2017). More studies are required to gain a fuller understanding of how resistant bacteria and antibiotics pass on and across different environments (e.g., soils, ponds, ground water) and are transferred between people and animals.…”
Section: The Rise Of Superbugsmentioning
confidence: 99%
“…The use of antibiotics is not only limited to clinical uses presently; large amount of it is used in Agriculture, Food industries, and Aquaculture (Van Boeckel et al, 2015). The environmental spread of unused antibiotics and their incomplete metabolism in the environment has elicited a bacterial adaptation response to develop antibiotic resistance and genes (Purohit et al, 2017). Antibiotics resistance in wastewater, surface water and drinking water has been documented (Purohit et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The environmental spread of unused antibiotics and their incomplete metabolism in the environment has elicited a bacterial adaptation response to develop antibiotic resistance and genes (Purohit et al, 2017). Antibiotics resistance in wastewater, surface water and drinking water has been documented (Purohit et al, 2017). The problem of antibiotic resistant bacteria is a global phenomenon in drinking water, rivers, lakes, groundwater and waste water (Mulamattathil et al, 2014).…”
Section: Introductionmentioning
confidence: 99%